Adding nickel formate in alkali lignin to increase contents of alkylphenols and aromatics during fast pyrolysis. (March 2017) - Geng, Jing; Wang, Wen-Liang; Yu, Yu-Xiang; Chang, Jian-Min; Cai, Li-ping; Shi, Sheldon Q.
Highlights: Adding nickel formate increased alkylphenols and aromatics. The higher temperature increased contents of alkylphenols and aromatics. The addition of nickel formate significantly enhanced the liquid yield. Reaction mechanism was proposed based on the experimental evidences. Abstract: The composition of pyrolysis vapors obtained from alkali lignin pyrolysis with the additive of nickel formate was examined using the pyrolysis gas chromatography-mass spectrometry (Py-GC/MS). Characterization of bio-chars was performed using X-ray diffraction (XRD). Results showed that the nickel formate significantly increased liquid yield, simplified the types of alkali lignin pyrolysis products and increased individual component contents. The additive of nickel formate increased contents of alkylphenols and aromatics from alkali lignin pyrolysis. With an increase in temperature, a greater amount of the relative contents can be achieved. The nickel formate was thermally decomposed to form hydrogen, resulting in hydrodeoxygenation of alkali lignin during pyrolysis. It was also found that Ni is in favor of producing alkylphenols. The analysis based on the experimental result provided evidences used to propose reaction mechanism for pyrolysis of nickel formate-assisted alkali lignin.